Design and fabrication of a cool box for passenger car using automotive air-conditioning system - Parvez Iqbal A.K.M.; Rahman M.M. (2023)
A cool box for passenger car refers to a kind of box which is designed and fabricated using well insulating materials in order to ensure the coolness inside the cool box is always stable. The coolness inside of cool box depends on the refrigerant cycles of the car air conditioning system. This cool box has same function as mini fridge to keep fresh foods and beverages but it cannot ensure to freeze the water because the temperature inside of the cool box will be in the range of 12.2C to 22.1C which is below the room temperature. This will help to minimize the activeness of bacteria to spoil the foods and beverages at the same time it can linger the duration for food and beverages to spoil. Cool box will help car users to bring food along them when traveling long journey and during the outdoor activities. The linkage system is mainly about connecting extra supplier hose at the receiver dryer section of car air conditioning system in order to intake the refrigerant flow to the cool box and back to connect at tube after evaporator section as outlet. All affecting parameter such as temperature inside the cool box, heat transfer rate, and air ventilation has been studied to design and fabricate the cool box. Finally several tests have been conducted which show that in operating condition inside temperature and relative humidity are suitable to keep the groceries items in fresh condition.